2020
DOI: 10.3390/cells9091933
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Feast and Famine in Cyanobacteria: Is Luxury Uptake of the Nutrient Just a Consequence of Acclimation to Its Shortage?

Abstract: To cope with fluctuating phosphorus (P) availability, cyanobacteria developed diverse acclimations, including luxury P uptake (LPU)—taking up P in excess of the current metabolic demand. LPU is underexplored, despite its importance for nutrient-driven rearrangements in aquatic ecosystems. We studied the LPU after the refeeding of P-deprived cyanobacterium Nostoc sp. PCC 7118 with inorganic phosphate (Pi), including the kinetics of Pi uptake, turnover of polyphosphate, cell ultrastructure, and gene expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 82 publications
2
17
0
Order By: Relevance
“…These results were in agreement with the results obtained by Solovchenko et al [ 46 ]; Koksharova et al [ 47 ] indicated that algal biomass productivity and its photochemical efficiency in addition to proteins and DNA repair enzymes are directly proportional to the nitrogen concentration.…”
Section: Resultssupporting
confidence: 93%
“…These results were in agreement with the results obtained by Solovchenko et al [ 46 ]; Koksharova et al [ 47 ] indicated that algal biomass productivity and its photochemical efficiency in addition to proteins and DNA repair enzymes are directly proportional to the nitrogen concentration.…”
Section: Resultssupporting
confidence: 93%
“…The ATP is needed for pumping of the polyphosphate into the microalgae cell and for the conversion of phosphorus to polyphosphate. The source of energy for ATP is the photosynthetic process and also respiration [ 2 , 28 , 45 ]. Table 3 shows microalgae cultivation related to various phosphorus content in the medium.…”
Section: Microalgae Nutrient Compositionmentioning
confidence: 99%
“…This cross-feeding relationship has been considered a key factor in stabilizing the long-term fermentation process in coculture systems [ 26 ]. Phosphorus (P) is an important nutrient central to storing and exchanging energy and information in cells [ 48 ]. Since part of the phosphate was used by E. coli in the coculture system, the remaining phosphate may be lower for cyanobacteria.…”
Section: Resultsmentioning
confidence: 99%